Comparison of cold knife cone biopsy and loop electrosurgical excision procedure in the management of cervical adenocarcinoma in situ: What is the gold standard? - Munro, A.; Leung, Y.; Spilsbury, Katrina; Stewart, C.; Semmens, James; Codde, Jim; Williams, Vincent; O'Leary, Peter; Steel, N.; Cohen, P.; Cohen, P. (Academic Press, 2015)
Objective: To compare the outcomes of patients with cervical adenocarcinoma in situ (ACIS) treated with cold knife cone (CKC) biopsy or loop electrosurgical excision procedure (LEEP) for the treatment of cervical adenocarcinoma in situ (ACIS). Study design: This is a retrospective, population-based cohort study of Western Australian patients with ACIS diagnosed between 2001 and 2012. Outcomes included pathological margin status and the incidence of persistent or recurrent endocervical neoplasia (ACIS and adenocarcinoma) during follow-up (b12 months) and surveillance (=12 months) periods. Results: The study group comprised 338 patients including 107 (32%) treated initially by LEEP and 231 (68%) treated by CKC biopsy. The mean age was 33.2 years (range 18 to 76 years) and median follow-up interval was 3.6 years (range b1 year to 11.8 years). Overall, 27 (8.0%) patients had ACIS persistence/recurrence while 9 (2.7%) were diagnosed with adenocarcinoma during the follow-up and surveillance periods. No patient died of cervical cancer within the study period. There were no significant differences in the incidence of persistent and/or recurrent endocervical neoplasia according to the type of excisional procedure. Patients with positive biopsy margins were 3.4 times more likely to have disease persistence or recurrence. Conclusion(s): LEEP and CKC biopsy appear equally effective in the treatment of ACIS for women wishing to preserve fertility. Patients undergoing conservative management for ACIS should be closely monitored, particularly if biopsy margins are positive in initial excision specimens. Patients and their clinicians should be aware of the potential risks of residual and recurrent disease.